Feasibility of an Exercise and CBT Intervention for Treatment of Depression: A Pilot Randomized Controlled Trial - Meyer, Jacob D.; Perkins, Seana L.; Brower, Cassandra S.; Lansing, Jeni E.; Slocum, Julia A.; Thomas, Emily B. K.; Murray, Thomas A.; Lee, Duck-chul; Wade, Nathaniel G. (Frontiers in Psychiatry, 2022)
Depression (DEP) is prevalent and current treatments are ineffective for many people. This pilot study’s purpose was to assess the feasibility, acceptability, and plausible efficacy of an 8-week intervention employing 30 minutes of prescribed moderate intensity exercise ('ActiveCBT') compared to 30 minutes of usual activities ('CalmCBT') immediately prior to weekly online CBT sessions. Ten adults with DSM-5-diagnosed current DEP were randomized to groups and completed: an intake assessment, eight weekly CBT sessions, final assessment, and 3-month follow-up. ActiveCBT participants were prescribed 30-minutes of moderate exercise immediately prior to each standardized 50-minute CBT session. CalmCBT participants continued with normal activities for 30 minutes before therapy. Questionnaires regarding DEP symptom severity (Patient Health Questionnaire-9 [PHQ-9]), between-session effectiveness (Behavioral Activation for Depression Survey [BADS], Automatic Thoughts Questionnaire [ATQ]), in-session effectiveness (Working Alliance Inventory-Short Revised [WAI]), and state anhedonia (Dimension Analogue Rating Scale [DARS], Visual Analogue Scale [VAS]; assessed 3 times: before Active/Calm condition, after, and after therapy) were completed each week. Therapy fidelity ratings were independently coded via a standardized codebook. The Structured Clinical Interview for DSM-5 (SCID) and Hamilton Rating Scale for Depression (HAMD) were used to assess DEP at intake, final, and 3-month follow-up. We found strong feasibility and acceptability (100% adherence, 100% retention at final visit, 74.6% therapy fidelity, and high patient satisfaction ratings). Differences between groups favoring ActiveCBT in anhedonia (DARS, Hedges’ g=0.92; VAS, g=3.16), within- (WAI, g=0.1.10), and between-session effectiveness (ATQ g=-0.65; BADS g=-1.40), suggest plausible efficacy of ActiveCBT for enhancing CBT. DEP rates were reduced in both groups from baseline to final (60% MDD SCID remission) and at follow up (Active: 40%; Calm: 25%). Larger and potentially quicker symptom improvement was found favoring the Active condition to the final visit (HAMD, between-group changes g=-1.33; PHQ-9, g=-0.62), with small differences remaining at follow-up (HAMD, g= -0.45; PHQ-9, g=-0.19). Exercise priming appears acceptable and plausibly efficacious for enhancing mechanisms of CBT and overall outcomes, though the present small sample precludes efficacy determinations. It appears feasible to conduct a randomized controlled trial comparing ActiveCBT to CalmCBT. Future trials evaluating this potentially promising treatment approach and mediating mechanisms are warranted.